Impact of Raman Amplifiers in the Mitigation of Turbulence in Free Space Optical Communication by Adaptive Optics - Nyambati, Onyambu Edwin; Macharia, Kiragu Henry; Ngoo, Livingstone M. H. (International Journal of Research in Interdisciplinary Studies, 2025)
Free-space optical communication (FSOC) presents a potent solution for next-generation networks, offering fiber-like bandwidth without the physical infrastructure. However, its performance is severely constrained by atmospheric turbulence, which induces signal scintillation and fading. This paper characterizes the atmospheric channel using the Gamma-Gamma (G-G) turbulence model, defined by the refractive index structure parameter (Cₙ²). The study develops a comprehensive MATLAB simulation platform to emulate FSOC system performance under various turbulence strengths and link distances. The mitigation strategy used; integrates adaptive optics (AO) for wavefront correction and distributed Raman amplification for signal gain. Results demonstrate that this hybrid approach significantly improves the system's resilience. Observing marked reduction in Bit Error Rate (BER) and an enhancement in Signal-to-Noise Ratio (SNR), effectively extending the viable operational range of FSOC systems. This enhanced reliability directly contributes to the practical deployment of FSOC as a cost-effective solution for bridging the digital divide in underserved and remote regions.